Customer Satisfaction on Starbucks Malaysia Post-Covid 19 Pandemic - Shing Yee Lim; Chenling Liang; Mingze Li; Minghao Liang; Smitha M. (AIBPM Publisher, 2022)
Due to the burgeoning competition in the retail coffee industry, standing out among numerous coffeehouse brand chains is crucial for Starbucks. Customers ever have more options to choose from and obtaining customer satisfaction is essential for Starbucks to stay in a winning position in the market. The COVID-19 pandemic, on the other hand, has altered everything, including how retailers serve their customers. This research examines whether service quality, perceived convenience, product, and promotion influence customer satisfaction post-Covid 19 Pandemic. A total of 185 participants have participated in the online survey via Google Forms and all data was analyzed using SPSS. The results show that service quality, perceived convenience, product and promotion positively impact customer satisfaction. These findings can provide meaningful insights and a few recommendations are suggested to Starbucks.